1997
DOI: 10.1038/bjc.1997.53
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between extracellular lactate and tumour pH in a murine tumour model of ischaemia-reperfusion

Abstract: Summary We have studied the relationship between extracellular lactate (LACTe) and extracellular pH (pHe) in murine tumours after vascular occlusion (clamping) followed by reperfusion. In tumours occluded at ambient room temperature, LACTe) measured by microdialysis, increased linearly with time and correlated strongly with the acidification of the extracellular compartment (r=0.97, P<0.03, n=4). Significant decrease in LACTe was evident following removal of occlusion at room temperature and is consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…The presence of additional factors that contribute to low pH in avascular regions of tumours is suggested by the recent results of Parkins et al (1997) who found a decline in extracellular pH after vascular occlusion of an experimental tumour. The initial decline in pH correlated with lactate production (under conditions in which carbon dioxide production was unlikely to occur), but the subsequent decline in pH was independent of lactate concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of additional factors that contribute to low pH in avascular regions of tumours is suggested by the recent results of Parkins et al (1997) who found a decline in extracellular pH after vascular occlusion of an experimental tumour. The initial decline in pH correlated with lactate production (under conditions in which carbon dioxide production was unlikely to occur), but the subsequent decline in pH was independent of lactate concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies of tumours grown from variant cells that are glycolysis deficient (because of decreased glucose uptake and phosphoglucose isomerase deficiency) and that produce negligible amounts of lactic acid showed that these tumours also had an acidic microenvironment (Newell et al, 1993). Values of pHe and lactate concentration have also been studied during periods of vascular clamping and reperfusion of an experimental tumour (Parkins et al, 1997). The initial fall in the pHe in the avascular tumour correlated with lactate production, but the subsequent continued fall in pHe did not.…”
mentioning
confidence: 99%
“…However, acidic pH and lactate have also been associated with enhanced metastatic tumour progression both in experimental models (Schlappack et al, 1991;Jang and Hill, 1997) and clinically (Parkins et al, 1997;Walenta et al, 2000;Brizel et al, 2001). We wanted to determine whether the glucose þ MIBG-based tumour-acidifying treatment, used to improve efficacy of cancer therapies, would affect the spontaneous metastatic potential of two murine tumour cell lines, KHT-C and B16F1, previously shown to increase their experimental metastatic potential following acidic culture conditions (Schlappack et al, 1991;Jang and Hill, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In separate studies, the ability of murine B16F1 melanoma and KHT fibrosarcoma cells to form lung metastases after intravenous injection was shown to increase significantly after exposure to acidic conditions in culture (Schlappack et al, 1991;Jang and Hill, 1997). In humans, elevated tumour lactate concentrations, which generally correlate with reduced pH e , have been found to predict the likelihood of metastatic disease in head and neck and cervical carcinomas (Parkins et al, 1997;Walenta et al, 2000;Brizel et al, 2001). In addition to upregulated expression of invasion-enhancing proteins such as gelatinases, this increase in metastases may be related to acidosis-induced elevation of interleukin-8 (IL-8) and/or vascular endothelial growth factor (VEGF), factors known for their angiogenic potential (Shi et al, 1999;Xu and Fidler, 2000;Fukumura et al, 2001;Shi et al, 2001).…”
mentioning
confidence: 99%
“…It is well known that lactate secretion by tumor cells is one of the important causes of acidification of the immediate microenvironment of primary tumors [70]. However, since primary mouse tumors derived from cells lacking lactate dehydrogenase are also capable of acidifying the tumor microenvironment [71], other mechanism(s) must be involved in regulating extracellular acidification during tumor progression.…”
Section: Ha/cd44mentioning
confidence: 99%